Metagenomics Reveals a Core Macrolide Resistome Related to Microbiota in Chronic Respiratory Disease - Mac Aogáin, Micheál; Lau, Kenny J. X.; Cai, Zhao; Kumar Narayana, Jayanth; Purbojati, Rikky W.; Drautz-Moses, Daniela I.; Gaultier, Nicolas E.; Jaggi, Tavleen K.; Tiew, Pei Yee; Ong, Thun How; Siyue Koh, Mariko; Lim Yick Hou, Albert; et al. (American journal of respiratory and critical care medicine, 2020)
Long-term antibiotic use for managing chronic respiratory disease is increasing; however, the role of the airway resistome and its relationship to host microbiomes remains unknown. To evaluate airway resistomes and relate them to host and environmental microbiomes using ultradeep metagenomic shotgun sequencing. Airway specimens from 85 individuals with and without chronic respiratory disease (severe asthma, chronic obstructive pulmonary disease, and bronchiectasis) were subjected to metagenomic sequencing to an average depth exceeding 20 million reads. Respiratory and device-associated microbiomes were evaluated on the basis of taxonomical classification and functional annotation including the Comprehensive Antibiotic Resistance Database to determine airway resistomes. Co-occurrence networks of gene-microbe association were constructed to determine potential microbial sources of the airway resistome. Paired patient-inhaler metagenomes were compared ( = 31) to assess for the presence of airway-environment overlap in microbiomes and/or resistomes. Airway metagenomes exhibit taxonomic and metabolic diversity and distinct antimicrobial resistance patterns. A "core" airway resistome dominated by macrolide but with high prevalence of β-lactam, fluoroquinolone, and tetracycline resistance genes exists and is independent of disease status or antibiotic exposure. and are key potential microbial reservoirs of macrolide resistance including the , , and genes. Significant patient-inhaler overlap in airway microbiomes and their resistomes is identified where the latter may be a proxy for airway microbiome assessment in chronic respiratory disease. Metagenomic analysis of the airway reveals a core macrolide resistome harbored by the host microbiome.